2015
DOI: 10.1016/j.ydbio.2015.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Budgett's frog (Lepidobatrachus laevis): A new amphibian embryo for developmental biology

Abstract: The large size and rapid development of amphibian embryos has facilitated ground-breaking discoveries in developmental biology. Here, we describe the embryogenesis of the Budgett’s frog (Lepidobatrachus laevis), an unusual species with eggs that are over twice the diameter of laboratory Xenopus, and embryos that can tolerate higher temperatures to develop into a tadpole four times more rapidly. In addition to detailing their early development, we demonstrate that, like Xenopus, these embryos are amenable to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 78 publications
(87 reference statements)
2
11
0
Order By: Relevance
“…The findings presented here are also important when considering the welfare and transportation of other aquatic amphibian model species such as X. tropicalis (Jafkins et al, 2012) or Budgett's frog (Lepidobatrachus laevis; Amin et al, 2015). Finally, many amphibian species are the subjects of conservation programs that involve translocation and reintroduction.…”
Section: Impactsmentioning
confidence: 86%
“…The findings presented here are also important when considering the welfare and transportation of other aquatic amphibian model species such as X. tropicalis (Jafkins et al, 2012) or Budgett's frog (Lepidobatrachus laevis; Amin et al, 2015). Finally, many amphibian species are the subjects of conservation programs that involve translocation and reintroduction.…”
Section: Impactsmentioning
confidence: 86%
“…The influence of this ontogenetic variation is most pronounced in the genus Lepidobatrachus . Indeed, because of its large size and rapid development, Lepidobatrachus laevis has recently been proposed as a model species in experimental studies undertaken to address a wealth of classic questions in amphibian embryogenesis [ 93 ]. Furthermore, because of its sympatry with several other ceratophyrid species (in the Gran Chaco of South America) and its well established phylogenetic relationship to those species [ 10 ], Lepidobatrachus stands out, not only as model species for studying developmental processes per se , but exceptional for studying the very evolution of those processes.…”
Section: Discussionmentioning
confidence: 99%
“…Embryonic development is rapid; embryos reach feeding stages in 2–3 days and increasing their body size by a factor of 6–8 times. The results of Amin et al () showed that embryos of Lepidobatrachus laevis share some features with Ceratophrys and Chacophrys ; among these are color and shape at tailbud stage, morphology of adhesive glands, number of external gills, early hatching, and an abbreviated larval development. However, young embryos of Lepidobatrachus are larger and have more yolk, and growth and development are faster than in other ceratophryids.…”
Section: Discussionmentioning
confidence: 99%
“…In embryos with slow development such as Gastrotheca riobambae , gastrulation takes about 2 weeks and body lengthening occurs postgastrulation (del Pino & Loor‐Vela, ). Conversely, in fast developers such as embryos of Xenopus and ceratophryids, gastrulation occurs in a few hours and overlaps with body lengthening ( C. ornata , C. stolzmanni , and L. laevis ; Amin et al, ; del Pino, ; Purcell & Keller, ; Santillana Ortiz & del Pino, ). Embryos of all species in our study also show some degree of overlap between the developmental events, as evidenced by elongated embryos with open blastopores.…”
Section: Discussionmentioning
confidence: 99%